Social capital, built environment and mental health: a comparison between the local elderly people and the 'laopiao' in urban China. Issue 1 (23rd January 2022) - Tang, Shuangshuang; Lee, Harry F.; Feng, Jianxi
Abstract: In rapidly urbanising China, a high number of elderly people, the so-called ' laopiao ', float to cities where their sons or daughters live to look after their children and grandchildren. Laopiao in urban China are thought to suffer poor mental health owing to their floating status. This study explores the inter-relationship among social capital, the built environment and mental health in urban China. Using a recent survey conducted in Nanjing (N = 591), structural equation modelling was performed to compare the local elderly people and the laopiao . Results showed that mental health determinants are dissimilar between the two groups of elderly people. Bonding social capital promotes mental health in both groups, while bridging and linking social capital only contributes to the mental health of the laopiao . Also, access to public transportation is positively correlated with mental health in both groups. Furthermore, lower street network density and better access to parks enhance the mental health of the local elderly people, while higher street network density and more open space within a community enhance the mental health of the laopiao . Our findings suggest that different policy measures should be implemented for different groups of elderly people in urban China to improve their mental health.